Improving procedural and one-year outcome after contact force-guided pulmonary vein isolation: the role of interlesion distance, ablation index, and contact force variability in the 'CLOSE'-protocol. Issue Volume 20:Issue FI 3(2018) (4th January 2018) - Phlips, Thomas; Taghji, Philippe; El Haddad, Milad; Wolf, Michael; Knecht, Sébastien; Vandekerckhove, Yves; Tavernier, René; Duytschaever, Mattias
Abstract: Aims: We have recently shown that a contact force (CF)-guided ablation protocol respecting region-specific criteria of lesion contiguity and lesion depth ('CLOSE' protocol) is associated with high incidence of acute durable pulmonary vein (PV) isolation (PVI) and a high single-procedure arrhythmia-free survival at 1 year. In the present study, we compared efficiency, safety, and efficacy of 'CLOSE'-guided PVI to conventional CF-guided PVI (CONV-CF). Methods and results: Fifty consecutive paroxysmal atrial fibrillation (AF) patients underwent PV encircling using a CF-sensing catheter targeting an interlesion distance (ILD) ≤6 mm and ablation index (AI) ≥400 and ≥550 at posterior and anterior wall ('CLOSE' group). Results were compared to the last 50 patients undergoing 'CONV-CF'. All patients underwent adenosine testing after PVI. Arrhythmia recurrence was defined as any atrial tachyarrhythmia (ATA) >30 s on Holter at 3, 6, and 12 months. Clinical characteristics did not differ. Contact force variability was comparable in between both groups (proportion of applications with intermittent contact 2% in 'CLOSE' vs. 1% in CONV-CF, P = 0.67). In the 'CLOSE' group, procedure time and radiofrequency (RF) time per circle were shorter (respectively 149 ± 33 min vs. 192 ± 42 min, P < 0.0001 and 18 ± 4 min vs 28 ± 7.5 min, P < 0.0001) and incidence of adenosine-proof isolation was higher (97% vs. 82%, P < 0.001). No complications were observed in the 'CLOSE' group, one tamponade in the 'CONV-CF' group. At 12 months, single-procedure freedom from ATA was 94% in 'CLOSE' vs. 80% in 'CONV-CF' group ( P < 0.05). In both groups, the majority of reconnections at repeat were associated with either ILD > 6 mm and/or AI < 400/550 (100% vs. 83%, P = 0.99). Conclusion: 'CLOSE'-guided PVI improves procedural and 1 year outcome in CF-guided PVI while shortening procedure time. Improvement cannot be explained by differences in CF variability and is most likely due to the strict application of criteria for contiguity and ablation index. A randomized controlled trial is needed to exclude the possible contribution of a learning curve.